Koniec „łużyckiego świata” - Czopek, Sylwester (Muzeum Okręgowe w Rzeszowie, 2022)
The article is devoted to the disappearance of the Lusatian cultural circle, also traditionally called the Lusatian culture or, in more recent literature, the Lusatian urnfields. At the beginning, terminological issues are clarified and views on the disappearance of this cultural unit, which played an important role in Central Europe in the middle of the 2nd and 1st millennium BC, are presented. The main analytical part focuses on four regions within today’s borders of Poland – north-western, north-eastern, south-western and south-eastern. This is due to the sharply outlined foreign cultural features that are particularly sharp in these regions. This applies to the infiltration of the Jastorf culture (and earlier Nordic influences), the Baltic circle, the Hallstatt cultural complex and the Eastern European nomadic world. They are the aftermath of migration movements of varying intensity and chronology, but always within the early Iron Age (9th/8th–5th centuries BC). Signs of the structural crisis of the local Lusatian communities, which are very fragmented and do not constitute a cultural monolith, are also important for the considerations undertaken. The issue of changes in the natural environment on the border of the subboreal and subatlantic periods is also considered.

After analysing issues related to terminology, chronology and the current state of research (especially in 4 crucial regions where there are clear external infiltrations leading to cultural changes), the following conclusions were formulated. I – it was indicated that in prehistoric studies it is generally easier to talk about the genesis and beginnings of cultural phenomena, especially in synthetic terms, than about their end. It is very significant that we often define it as a terminus ante quem in relation to the well-dated next settlement and cultural phase in a given area. Searching for direct source evidence, especially at the level of material culture, is difficult and generally fruitless (vide! the example of cultures with a model typical of the younger Pre-Roman Period). II – it was emphasized that at the beginning of the Early Iron Age, the ecumene of the Lusatian cultural circle cannot be considered homogeneous. Divisions into smaller regional units are a fact (regardless of whether we call them Lusatian groups, subgroups or local units of Urnfields), and during the relatively long period of their function, there is no indication that these differences are blurring. On the contrary, many observations suggest otherwise. This was important during the period of transformations and the emerging local distinctiveness, even reflecting the hallmarks of cultural differences. Obviously, it is difficult to conclude that this was the only reason for the emerging dissimilarities. The external „identifiers” of cultural changes show the greater driving force than the sedentary and passive Lusatian communities. The question about the impact of external, independent factors should be considered which could be significant enough to cause the crisis of the Lusatian communities. The role of environmental changes, which are most visible in the settlement structures of central Poland, including Biskupin, cannot be denied. They probably had an impact on the functioning of some Lusatian populations. The „political” aspects that we can notice in the creation of the Chotyniec agglomeration, belonging to the Scythian circle, are also proven. III – cultural changes and modifications took place dynamically, but we are not always able to chronologize them precisely, and consequently compare and interpret them, as we still operate within the three centuries of the Early Iron Age with various absolute dates of the individual phases of HaC and HaD. Karol Dzięgielewski has presented recently a successful attempt to synchronize cultural phenomena with climate changes, separating 3–4 stages, the most important of which is the identification of the period between 650 and 500/450 BC (= HaD), defined as the time of more favourable climatic conditions for settlement, dividing the cooler and wetter phases - around 800-650 (= HaC) and 450 and later (= LtA-LtB). The pause in warming period synchronises well with the HaD, which corresponds to the period of the virtual and final phase of cultural changes, which consequently marked the beginning of the end of the Lusatian world. However, we cannot talk about a sharp caesura, because in many regions the thesis about the temporary coexistence of groups (settlement on a microscale) belonging to the Lusatian and Pomeranian cultures is strongly emphasized. IV – cultural changes in the Early Iron Age cannot be well understood without accepting the thesis of key importance about external influences which were related with population migrations. Certainly, they were of different nature, scale and intensity. It is worth mentioning, however, that the very concept of migration is not unambiguous and almost never means complete population replacement. Nevertheless, there is no doubt that the Early Iron Age in the Polish lands was a period of dynamic changes, with smaller or larger consequences for local Lusatian communities, which is a feature of the entire „Urnfield world”, and even more broadly, the reconstruction of the cultural order in almost entire Europe, which is exemplified, for instance, by the great Greek colonization. The presence of military migrations of Eastern European nomads from the 10 th /9 th century BCE also raise no doubts to Central and Southern Europe, regardless of their reasons. Therefore, it is difficult to negate the military Scythian invasions that affected some Lusatian groups from the western part of Poland. They are confirmed by sources (Wicina) and probably had consequences for the scale of the continued existence of the stable Lusatian settlement in the western part of Poland. V – apart from the key question about the cause – to simplify: migration or acculturation – many elements seem to indicate a general line of changes, in which its essence leads to various degrees of social differentiation. This phenomenon has the hallmarks of influences from the circle of culture with a higher material level and social organization in relation to local groups. This explains the presence of a new elite stratum, as well as material and symbolic emphasis on differences in social status, gender or age. They can take various shapes and forms, more or less clear in the sources (e.g. the Hallstatt type in Silesia), but their presence in the Early Iron Age is undoubtful. Therefore, if they are considered crucial changes, they can be described in this aspect as the end of the non-egalitarian Lusatian culture. The Silesian case indicates that after the period of these changes we are dealing with a certain stage that can be defined as the revival of old traditions (phase VI in Kietrz) or the weakening (perhaps even the diversion) of the previously outlined cultural features that differentiate society. An example may be the evolution of the funeral rite of the Pomeranian culture towards egalitarianism. VI – the consequence of the characterized changes, with chronological differences and their intensity, is the general conclusion that the decline of the Lusatian world can be characterized as multi-faceted, emphasizing earlier differences in settlement, economy, beliefs and material culture at the level of local structures. It is most readable as a cultural crisis. Observations of many local groups clearly indicate regional and even local differences, hence the great difficulty (or even inability) in constructing a general (one) model of the decline of Lusatian communities. It is basically impossible to formulate in the face of many different internal and external factors. Therefore, in this context, in fact, it is impossible to go beyond the proposals of our masters. We can only make additions, formulate new arguments which, even in the face of new and groundbreaking discoveries, do not change the fundamental conclusion regarding the decline as a process stretched over time, a forced or chosen way of transforming local communities. The term of the era of urned cremation is not considered to be synonymous with a population crisis. There is no evidence or even a coherent concept regarding a possible depopulation. VII – about a thousand years of dominance of the Lusatian world in Central Europe ended in completely different conditions than those that were clear at the time of its genesis and formation. Admittedly, also at that time, connections with other cultural groups were of great importance, which we combine into the Urnfield cultural circle. However, the direction of these inspirations was one – the broadly understood south. The substrate on the basis of which the Lusatian community developed was also similar to other Urnfield provinces (mainly the Tumulus cultures and related). For a thousand years, however, very serious changes took place, and in the entire area occupied by Urnfield cultures, at the end of their duration, we observe clear internal crises, caused by various factors (e.g. climate changes or social evolution). For the second time (apart from the Late Neolithic period) we are dealing with a visible pressure on Central Europe of Eastern European cultures and peoples. Sometimes it even took the form of devastating military escapades. What is more, the cultures that grew up in the northern Nordic circle, which had been stable for many centuries, also started to expand. The end of the „Lusatian world” should be synchronized with changes of much broader territorial connotations (one can say that they are even pan-European). It is a foreshadowing somewhat of what will happen in Central Europe over the next centuries.
The end of “the Lusatian world”
Niniejszy tekst jest nieco zmienioną wersją wystąpienia konferencyjnego pod tym samym tytułem, wygłoszonego w trakcie sympozjum „Ziemie polskie i ich sąsiedzi w czasach pól popielnicowych”, Lublin 21–23, wrzesień 2022.
Keywords: Lusatian culture; early Iron Age; disappearance of culture; migrations